Pengaruh Ketersediaan Sarana dan Prasarana Pendidikan terhadap Prestasi Belajar Siswa Kelas X TKR SMK Negeri 2 Siatas Barita Tahun Ajaran 2023/2024 - kristian Simanjuntak (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2024)
The aim of this research is to determine the effect of the availability of infrastructure on the learning achievement of class X TKR students at SMK Negeri 2 Siatas Barita. The method used in this research is an inferential quantitative method. The population was all 127 class X TKR students and a sample of 30 was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a closed questionnaire with 15 items. The results of data analysis show that there is a positive and significant influence in the availability of educational infrastructure on the learning achievement of class A positive relationship is obtained by the value rxy = 0.553 > rtable(=0.05,n=30) = 0.361, thus it is known that there is a positive relationship between variable > t table(=0.05,dk=n-2=28)= 2.048, thus there is a significant relationship between variable